Designing Data Warehouse in Finance Company Study at PT ABC - Rahadi, Putu Suta Adya Dharma; Widiadnyana, Putu; Sweden, Nengah (International Journal of Engineering and Emerging Technology, 2017)
Along with the development of technology and business needs that are more advanced, the more effective and efficient uses of Information Systems is an important thing for companies to continue competing in the era of globalization. Every company wants an appropriate Information System to run business activities smoothly. Using data warehouses can help PT ABC's problems in accommodating large amounts of data with its OLTP system which can then be processed in determining future strategies through OLAP systems. So as to get the reports needed in maintaining the consistency and improve the performance of the company.